Defining the Hourglass Framework of Technical and Musical Concepts in Music Technology Education with Two Case Studies in Course Development - Timothy Hsu (Journal of the Association for Technology in Music Instruction, 2022)
As the field of music technology connects music with a vast array of technical fields, a mature music technology program ideally challenges and develops students that incorporate musical contexts of technical ideas and the technical concepts of musical ideas. The educational challenge of music technology programs lies in the balancing of technical and musical material in the curriculum. In structuring this balance, this paper proposes an hourglass framework, where music technology sits at the neck of two sides, where one side is built on the tradition of Western and non-Western music history, theory, and repertoire, and the other side is constructed based on the development of engineering, computer science, design, physics, and other technical fields. This paper defines and discusses this hourglass framework, shows the curricular need, and presents two case studies of an undergraduate and a graduate course that employ balance through the hourglass framework. Through audio circuits, physics of sound, and acoustics synthesized with musical contexts, students discover and learn how technical concepts directly impact musical decisions, and vice versa. This paper discusses not only the methods employed by both classes, but also possible growth areas for continual improvement in exploring the intersection of technical and musical concepts.
Keywords: music technology education; audio circuits; acoustics; technical curriculum development; interdisciplinary studies